CONFLICTOLOGY AND NEGOTIATION THEORY - Мандрыка, В.; Секунова, Юлия (SWorldJournal, 2020)
Civic life cannot exist without conflicts of ideas, positions of life, goals of both individuals and collectives. Usually, conflict in the social and labor sphere is perceived as not a normal phenomenon. The article deals with science, called conflictolog